Efficient Photodegradation of Methylene Blue using WLED with Nanosphere Graphitic Carbon Nitride Compared with its Bulk Counterpart - Sarmah, Pingal; Gogoi, Sonit Kumar (Asian Journal of Chemistry, 2023)
Herein, a simple solvothermal synthesis of graphitic carbon nitride nanosphere (g-CNN) at 180 ºC is reported. The photocatalytic activity of g-CNN was studied under an in-house developed white light emitting diode (WLED) reactor and characterized by FESEM, PXRD, FTIR, EDX, UV-visible spectroscopy and BET isotherm. The g-CNN has absorbance in visible light region and exhibits enhanced photocatalytic activity compared to bulk graphitic carbon nitride (BGCN) for photodegradation of methylene blue, which attributes to its lower surface area. The photocatalytic performance of g-CNN as function of pH of dye solution and catalyst amount were also studied. The g-CNN can be used for three repeated cycles with minimal change in photocatalytic efficiency. The solvothermal synthesis method at relative low temperature introduces terminal oxygen functionalities in g-CNN, which enhance light absorption and accelerate electron transfer results in improvement of photocatalytic efficiency of g-CNN. The results demonstrated the effectiveness of g-CNN as a photocatalyst for the treatment of water using visible light from WLED.